Toward a Theology of Divine Action: William R. Stoeger, S.J., on the Laws of Nature. (September 2015) - Edwards, Denis
In the 1990s William Stoeger, S.J., contributed major essays on the laws of nature to the series of conferences on divine action that were cosponsored by the Vatican Observatory and the Center for Theology and the Natural Sciences at the Graduate Theological Union Berkeley, CA. He argued that the laws of nature are to be seen as approximate models rather than as complete descriptions of nature, and that they are descriptive rather than prescriptive. These essays, Denis Edwards proposes, are an important legacy for 21st-century theology and offer creative possibilities for a renewed theology of divine action that builds on the Thomist tradition.